Analysis of non-destructive testing of three-dimensional braided composites based on SQUID. Issue 1 (2nd January 2017) - Wang, Zhangang; Zhang, Shuya; Wan, Zhenkai; Zhang, Meiling
Abstract: A non-destructive testing (NDT) system based on a superconducting quantum interference device (SQUID) is used for detecting the electromagnetic properties of three-dimensional (3D) braided composites. Samples with artificial defects are detected via artificial neural network and the flux imaging methods; the results compared well. Experimental results indicate that the SQUID-based NDT technique is far more advanced and practical for three-dimensional (3D) braided composites.